The Role of Multilingual Education in Enhancing Cognitive Development in Bilingual Children - John Cumberbatch; Alicia Cumberbatch (International Journal of Multilingual Education and Applied Linguistics, 2024)
This article explores the cognitive benefits of multilingual education, particularly focusing on bilingual children. By reviewing existing literature on language acquisition, cognitive flexibility, and executive function, the study examines how exposure to multiple languages can enhance children's problem-solving abilities, memory, and attention span. The research emphasizes the importance of implementing multilingual education strategies in early childhood education to foster cognitive development and better prepare children for a globalized world.